2001
DOI: 10.1016/s0014-5793(01)02108-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of vimentin head domain inhibits interaction with the carboxyl‐terminal end of α‐helical rod domain studied by surface plasmon resonance measurements

Abstract: The amino-terminal head domain of vimentin is the target site for several protein kinases and phosphorylation induces disassembly of the vimentin intermediate filaments in vivo and in vitro. To better understand molecular mechanisms involved in phosphorylation-dependent disassembly, we examined domain interactions involving the head domain and the effect of phosphorylation on the interaction, using surface plasmon resonance. We observed that the head domain binds to the carboxyl-terminal helix 2B in the rod do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This implies interactions between the head domain and rod 2B, and evidence exists to support this (48, 49). Binding affinity measurements have placed this head domain/2B interaction in the far carboxy terminus of region 2B in residues 390-411 a highly conserved region spanning the Helix Termination Motif.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This implies interactions between the head domain and rod 2B, and evidence exists to support this (48, 49). Binding affinity measurements have placed this head domain/2B interaction in the far carboxy terminus of region 2B in residues 390-411 a highly conserved region spanning the Helix Termination Motif.…”
Section: Discussionmentioning
confidence: 92%
“…Binding affinity measurements have placed this head domain/2B interaction in the far carboxy terminus of region 2B in residues 390-411 a highly conserved region spanning the Helix Termination Motif. Surface plasmon resonance measurements showed that this interaction is substantially lowered, and possibly eliminated, when the vimentin head domain is phosphorylated in vitro with PKA (48). Additional studies identified the ability of arginine but not lysine to interfere with filament assembly and the identification of the di-arginine motif in the head as critical for IF assembly offers an explanation (49, 50).…”
Section: Discussionmentioning
confidence: 99%
“…To that end, several in vitro studies demonstrate the importance of the ordered assembly of filaments (29), and of intrinsic determinants within IF proteins, for their organization (4,30). Among these determinants are interactions of the head-and-rod domains, which can be modulated by phosphorylation as demonstrated by phosphorylation-mediated inhibition of purified vimentin head-domain interaction with helix 2B of the rod domain (31), supporting the hypothesis that keratin (and likely other IF proteins) filament organization and reorganization are hierarchical and involve multiple phosphorylation͞dephosphorylation events that may be coupled to associations͞dissociations with other IF-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These residues are located in the head domain of vimentin, and modification of residues in the head domain prevents vimentin from forming higher order structures 148 . ADP-ribosylation likely blocks vimentin oligomerization into intermediate filaments, resulting in disruption of vimentin filaments and cytoskeletal collapse 147 .…”
Section: C3-like Toxinsmentioning
confidence: 99%